Analysis Semiotic of the Movie Siksa Neraka By Anggy Umbara (Semiotic Analysis of Charles Sanders Pierce) - Khafita, Khafita Aini; Ahmad Tamrin Sikumbang (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
ABSTRACT The film can be used in preaching. This research aims to analyze the preaching messages in the movie